Peningkatan Hasil Belajar IPA Pada Siswa Kelas VI SDK Wologeru Melalui Model POE (Predict Observed Explain) - Gerardus Ghlae (Ekspektasi: Jurnal Pendidikan Ekonomi, 2022)
This research is classroom action research which is carried out in two cycles. The purpose of this study was to determine the increase in science learning outcomes with the implementation of the Predict-Observe-Explain (POE) model in science subjects for class VI SDK Wologeru. The research subjects were 9 students of class VI SDK Wologeru. The method of data collection in this study was carried out by the method of test, observation and documentation. The data collected were analyzed by quantitative descriptive techniques. The results showed that the percentage of science learning outcomes for fifth grade students in the first cycle was 33 percent. In cycle II, the percentage of science learning outcomes for grade VI students increased to 100 percent. Based on the results of this study, it can be concluded that the Predict–Observe-Explain (POE) learning model can improve science learning outcomes for grade VI students of the SDK Wologeru.